Prognostic personality indicators of perfectionism in early adulthood - Sokolovich, Еkaterina А. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Perfectionism is a stable personality style, which is characterized by excessively high standards and the significance of achievements, exactingness, lack of ability to adequately assess the capabilities of oneself and others, intolerance to mistakes. The following techniques were applied: the multidimensional scale of perfectionism Hewitt and Flett in the adaptation of I. I. Gracheva, psychodiagnostic test Melnikova and Yampolsky, a technique for diagnosing a personality on the motivation for success of Ehlers, a technique for diagnosing a personality on the motivation for avoiding the failures of Ehlers, the Dembo – Rubinstein technique for diagnosing levels of self-esteem and claims in the modification of P. V. Yanshin. As a result of the study: various individually-personal and motivational characteristics are factors of the appearance of different types of perfectionism. These results can be used in psychotherapy and counseling when working with students and young professionals who are extremely demanding of themselves and others.
Keywords: perfectionism; self-oriented perfectionism; object-oriented perfectionism; socially prescribed perfectionism; individually-personal characteristics; motivational characteristics; early adulthood